Side effect profile of hepatitis C treatment with peginterferon alpha-2b and ribavarin - Mubashir, Syed; Gul, Irfan; Rasool, Abid; Gul, Shujat; Gulzar, G. M.; Wani, Muzamil Ahmad (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The major types of side effects include fatigue, influenza-like symptoms, gastrointestinal disturbances, neuropsychiatric symptoms and hematologic abnormalities. These side effects may be treatment limiting and require dose reduction or drug discontinuation objectives of the study was to assess the side effect profile of hepatitis C treatment (peginterferon alpha-2b and ribavarin) in Kashmiri patients attending the Department of Gastroenterology skims. Methods: In this study, all consecutive patients of hepatitis C infection on peginterfron and ribavarin treatment were enrolled after written consent. The patients underwent intervention treatment taking pegylated interferon α-2b (Viraferon, Schering Plough Corp., Kenilworth, NJ) and ribavirin in accordance with the standard protocol. Patients were monitored through weekly referrals while taking the medications. A detailed history was taken and complete physical examination done each time the patient presented to the hospital necessary blood sampling was taken. Results: During the study period of 2 years,105 Patients were enrolled 55 (52.4%) were males with a male:female ratio of 1.1:1.0. and mean age 37.6 years with a range of 13-75 years 7 patients (6.6) had a history of needle pricks, 4 patients (2.2%) of sharing same razors at barber’s shop. 4 (3.8%) patients of drug abuse; out of which 3 (2.8%) were intravenous drug abusers, Anemia occurred in 17 (16.2%) patients with requirement of dose modification w in 11 (10.4%) patients and dose stoppage in 1 (0.95%) patient in whom Hb dropped to less than 7, thrombocytopenia occurred in 27 (25.7%) patients with requirement of dose modification in 13 (12.3%) patients and dose stoppage in 1 (0.95%) patients due to platelet count decreasing to less than 30,000. Neutropenia as defined by ANC less than 1500 occurred in 22 (20.9%) patients. Conclusions: Dose modification was required in 48 (45.7%) patients, 30 (28.5%) patients required dose modifications due to labortory abnormalities and 18 (17.1%) due to other side effects. In 8 (7.6%) patients dose was discontinued due to adverse events (including psychosis in 1, severe flu like symptoms in 3, dermatitis in 1, depression in 3).